Effect of β-glucan fortification on physico-chemical, rheological, textural, colour and organoleptic characteristics of low fat dahi - Bhaskar, Dadi (J Food Sci Technol, 2017)
Fortified low fat functional dahi prepared by supplementing skimmed buffalo milk with β-glucan (0.25, 0.50, 0.75 and 1.0%) was assessed for physico-chemical, rheological, textural, colour and sensorial characteristics. Total solids in dahi increased significantly with the increase in β-glucan concentration, however, values of fat, protein and ash varied non-significantly upon β-glucan addition in dahi. β-glucan at 0.5% solids levels, produced low fat dahi with superior quality, less whey separation and good textural properties than the samples containing other levels. Syneresis and viscosity was positively affected with the addition of β-glucan till 0.5% level and higher concentration caused destabilization of the product. Fortified dahi showed greater firmness and consistent than control dahi sample. The addition of 0.5% level of β-glucan also imparted significantly better instrumental color values and sensory scores with attractive or natural dahi color when compared to control dahi samples and other dahi samples prepared with different levels of β-glucan.